Intra-Party Crises, Defections and Electoral Performance in 2015 General Elections in Kwara State, Nigeria - Moliki, Ahmed Olawale (NIU Journal of Social Sciences, 2020)
The paper assessed the effects of intra-party crises and defections on party performance during the 2015 General Elections in Kwara State, North-central Nigeria. Data obtained from secondary sources were content analysed. The paper observed that there has been unmanageable trend of internal crises within the Nigeria’s political parties in contemporary times, gradually polarising and distorting party politics. Series of these internal squabbles seemingly uncontrollable have contributed to the conundrums of defections experienced in the major and minor political parties in most states of the federation, Kwara State, inclusive. So alarming is the situation that elections are competed for like warfare with consequences for electoral outcomes. Our major findings indicated that patron-client politics, factionalism, poor party internal democracy and ideologies, money politics, and overambitious character of party leadership occasioned intra-party crises and defections in Kwara State. It further established that intra-party feuds and defections within the Peoples’ Democratic Party (PDP) towards the 2015 General Elections led to its woeful performance while conversely contributed largely to the brilliant performance of the All Progressives Congress (APC) in the elections. The paper concluded that party members should be enlightened on moral politics, internal democracy and Inter-Party Advisory Council (IPAC) should be strengthened with a view to timely engaging the political actors involved in internal crisis and resolve their disagreements amicably. Keywords: Defection, Internal Crisis, Party Politics, Performance, Kwara Politics